Mega‐Depressions on the Cocos Ridge: Links Between Volcanism, Faults, Hydrothermal Circulation, and Dissolution - Jared W. Kluesner; Eli A. Silver; Nathan L. Bangs; César R. Ranero; Stephanie Nale; James Gibson; Kirk D. McIntosh (Geochemistry, Geophysics, Geosystems)
Abstract High‐resolution bathymetry and three‐dimensional seismic data along the Cocos Ridge reveal a 245 km2 field of ∼1–4 km in diameter seafloor depressions. The seafloor depressions are part of a two‐tiered honeycomb pattern. The lower‐tier depressions have steep faults that truncate strata with chaotic internal reflections consistent with sediment collapse into the depression. These extend into a lens shaped interval just above igneous basement. Overlying these depressions is a second broader set with rough seafloor morphology with gently dipping boundaries defined by pinch‐out stratigraphic patterns. Drilling results indicate that the lens‐shaped zones that host the deeper depressions represent anomalous regions of high porosity, low velocity, and low density within calcareous rich sediment. Analysis of nannofossils from IODP Site U1414 suggests the collapse structures formed during the late Miocene, whereas the younger shallower depressions likely formed between the early Pliocene and the Pliocene‐Pleistocene boundary. Geochemical and petrological analysis at Site U1414 suggests that hydrothermal circulation during the late Miocene led to carbonate dissolution and collapse. Following collapse, focused fluid‐flow and bottom current scouring resulted in formation of the overlying set of depressions and a honeycomb seafloor morphology. Similar sets of depressions along the Carnegie Ridge to the south support the hypothesis that two‐tiered depressions formed in response to processes that occurred broadly across the Panama Basin between the late Miocene and the Pliocene‐Pleistocene transition. Geochemical results at Site U1414, combined with geophysical data, suggest this two‐tiered system of depressions currently guides ongoing fluid outflow.